Framing Gemoy Paslon Prabowo-Gibran untuk Meningkatkan Ketertarikan Pemilih Pemula : Studi Kasus di Desa Kalang, Kecamatan Sidikalang, Kabupaten Dairi (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study examines the "Gemoy" (adorable) framing strategy applied to the Prabowo-Gibran candidate pair in the context of Indonesia's General Election, focusing on efforts to increase the interest of first-time voters. The study aims to analyze the potential of using a lighter, more relaxed, and relatable image as an alternative approach to political campaigning. The initial findings suggest that the "Gemoy" framing can bridge the perception gap between senior politicians like Prabowo and the 17-21 age demographic, while positioning Gibran as a representation of youth aspirations. This approach helps soften Prabowo’s image, which is typically seen as stern and rigid, and makes him more approachable. Gibran, on the other hand, symbolizes the connection to the younger generation. This framing strategy has proven effective in making the once tense and formal image of the candidate pair more simple and engaging for the youth demographic. The research uses a field research method with a qualitative approach. The study focuses on first-time voters in Desa Kalang, Kecamatan Sidikalang, Kabupaten Dairi, as key informants. Data was gathered through primary and secondary sources, including in-depth interviews, participatory observation, and documentation. The key informants included first-time voters, community leaders, campaign team members, and political communication academics.Data analysis followed three stages: data reduction, data presentation, and verification/conclusion. The study results show that the "Gemoy" framing strategy for the Prabowo-Gibran pair was highly effective in increasing the interest of first-time voters in Desa Kalang. It successfully simplified their image from initially appearing tense and rigid into one that is more relatable and appealing through the "Gemoy" framing.